PENGARUH SUKU BUNGA (BI RATE), EPS DAN ROE TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Nor Dewi; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2016)
The capital market is one of the sources of funding for the company, as well as a place for investors to invest. One of the business sector that profitable to invest is the mining sector. However, since early 2014 the stock performance of the mining sector decreased and it will have an impact on stock prices of the mining sector in the next year. The population of the research are 39 companies of the mining sector listed in Indonesia Stock Exchange ( IDX ) during period 2010-2014. The research data is obtained on secondary data from the financial statements published by the Indonesia Stock Exchange (IDX). The sampling process by using purposive sampling method in which only mining company listing and active in a row during the period 2010-2014 who willing provide the necessary data in research. Total samples that suitable the criteria as much as 17 mining companies. The analysis technique used linear regression. Hypothesis testing using t-test and F-test with significant level 5%. The result of the research indicates only Earning Per Share ( EPS ) partially has a significant effect on the Stock Price of the mining sector. While BI Rate and Return On Equity ( ROE ) has no significant effect on the Stock Price of the mining sector. Simultaneously, Bi Rate, Earning Per Share ( EPS ) and Return On Equity ( ROE ) has significant effect to the Stock Price of the mining sector. For further research, It better to add another variable that could affect stock price, using a wider research object with a longer study period. For issuer, they should improve the performance and evaluate management performance every year periodically. For investor, they should pay attention to the internal and external factors companies like interest rate, eps, roe before making a decision to invest.